Impact of Orthodontic Brackets on the Intraoral Scan Data Accuracy. - Park, Ji-Man; Choi, Shin-Ae; Myung, Ji-Yun; Chun, Youn-Sic; Kim, Minji (BioMed Research International, 2016)
This study aims to compare the impact of buccal and lingual brackets on the accuracy of dental arch data acquired by 4 different digital intraoral scanners. Two pairs of dental casts, one with buccal brackets and the other with lingual brackets, were used. Digital measurements of the 3D images were compared to the actual measurements of the dental models, which were considered standard values. The horizontal measurements included intercanine widths and intermolar widths. The Mann–Whitney U test was performed for comparisons. iTero® and Trios® both showed high accuracy with relatively small maximum deviation of measurements. iTero showed a significantly higher accuracy in most of the arch width measurements on the buccal bracket model than on the lingual model (P<0.05). Zfx IntraScan® and E4D Dentist® produced maximum deviations of more than 2 mm from both the buccal and the lingual bracket models. After comparing the degree of distortion of the arch on the digital scans with actual measurements of the same models, iTero and Trios proved to be excellent in terms of trueness and precision. Nevertheless, digital intraoral scanners should be used more cautiously in arches with lingual brackets than in those with buccal brackets.